A Comparative Study Of Lichtenstein Mesh Repair (LMR) v/s Modified Bassini’s Repair (MBR) + MESHPLASTY of Indirect Inguinal Hernias in Rural Population - Raghuwanshi, Dr.Pratikshit; Gharde, Pankaj (International Journal of Psychosocial Rehabilitation, 2020)
Background: Inguinal hernia is one of the biggest challenges in surgical practice because of its frequency, complexity as well as the socio-economic consequences. Inguinal hernia repair is the only cure; spontaneous recovery has never been reported. There are many techniques of hernia repair but most effective and commonly done are Lichtenstein’s repair and modified bassini’s repair with meshplasty. This study is being done to see the recurrence rate and post operative complication in the two groups of inguinal hernia patients one with Lichtenstein’s repair and modified bassini repair with meshplasty. Objectives- To study the recurrence rate among both groups,to study the factors which lead to recurrence,to evaluate operative time in both procedures. Methodology-Patients will be divided in two groups, one group will be operated by lichenstein repair and other will be operated by modified bassini repair and meshplasty. The patients will be followed up postoperatively after 6 months by clinical examination and USG inguinoscrotal region for hernia recurrence. Results-The results expected in the end of the study are that the risks of recurrence may be less in both the groups with almost the same incidence of recurrence in both the groups. Conclusion-It may be concluded that both the surgical procedures for inguinal hernia repair are effective equally with less chances of recurrence and complications